Groundwater dynamics and quality under intensive cropping systems - Gumtang, R.J.; Pampolino, M.F.; Tuong, T.P.; Bucao, D. (Cambridge University Press, 1999)
A study was conducted from October 1994 to March 1996 to assess groundwater dynamics and quality in relation to landuse and farm input of nitrogen fertilizer in a highly diversified and intensive agricultural area at Magnuang, Batac, Ilocos Norte. Monthly groundwater depths, nitrate-nitrogen (NO3-N), chloride (Cl−), bicarbonate (HCO3−), electrical conductivity (EC) and pH were determined in 19 agricultural and domestic wells. In the dry season, sweet pepper (Capsicum annuum) had a higher irrigation requirement and caused more groundwater level decline than other crops. EC (700–3000 μmho cm−1) and HCO3− (90–500 ppm) in all wells exceeded the FAO threshold quality for irrigation but were not related to farm management practices. Eight wells showed near or above the World Health Organization NO3-N limit (10 ppm) for drinking water. High nitrogen fertilizer input increased the mean NO3-N (r2 = 0.45, p < 0.002). The percentage of the wells' service area under rice cultivation in the wet season accounted for 84% (p < 0.001) of the variation in NO3-N among the wells. The mean NO3-N declined as the percentage of service area under rice increased. This was related to the denitrification process in the flooded fields and the lower levels of nitrogen fertilizer for rice compared with other crops.